2001
DOI: 10.1007/s002210100776
|View full text |Cite
|
Sign up to set email alerts
|

The neurophysiological substrate for the cervico-ocular reflex in the squirrel monkey

Abstract: Passive rotation of the trunk with respect to the head evoked cervico-ocular reflex (COR) eye movements in squirrel monkeys. The amplitude of the reflex varied both within and between animals, but the eye movements were always in the same direction as trunk rotation. In the dark, the COR typically had a gain of 0.3-0.4. When animals fixated earth-stationary targets during low-frequency passive neck rotation or actively tracked moving visual targets with head movements, the COR was suppressed. The COR and vesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 59 publications
5
40
1
Order By: Relevance
“…Studies in squirrel monkey have suggested that EH neurons respond to changes in neck position or velocity during passive rotation of the monkey's body with its head-held stationary in space (Gdowski and McCrea 2000;Gdowski et al 2001). In contrast, when we tested neurons with a comparable paradigm in the present study, we found no influence of passive neck activation in rhesus monkeys (Fig.…”
Section: Eh Neurons Are Not Influenced By Passive Neck Proprioceptivecontrasting
confidence: 74%
See 4 more Smart Citations
“…Studies in squirrel monkey have suggested that EH neurons respond to changes in neck position or velocity during passive rotation of the monkey's body with its head-held stationary in space (Gdowski and McCrea 2000;Gdowski et al 2001). In contrast, when we tested neurons with a comparable paradigm in the present study, we found no influence of passive neck activation in rhesus monkeys (Fig.…”
Section: Eh Neurons Are Not Influenced By Passive Neck Proprioceptivecontrasting
confidence: 74%
“…Studies in alert squirrel monkey have suggested that most second-order neurons in the medial vestibular nuclei including EH neurons are influenced by passive activation of neck proprioceptors McCrea 1999, 2000;Gdowski et al 2001). In contrast, our recent studies in rhesus monkey have found no evidence that second-order neurons within the medial vestibular nuclei are influenced by neck proprioceptive inputs Cullen 2001, 2002).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations